The Strategic Resistance of Muhammadiyah Green Cadres in the Wadas Socio-Ecological Conflict - Muhammad Aidrus Asyabani; Danang Puji Atmojo (Talenta Publisher, 2026)
State-led infrastructure projects in the Global South often trigger conflicts, yet the role of religious actors remains under-theorized. This study examines how Kader Hijau Muhammadiyah (KHM) navigates 'shrinking civic space' in Indonesia’s Wadas mining conflict. Employing a qualitative approach with elite sampling and document triangulation, the research analyzes KHM’s 'triad of resistance': science-based advising, confrontational advocacy for the marginalized (mustad'afin), and 'inside-track' lobbying. Although entrenched oligarchic interests prevented the mining permit's revocation, KHM successfully disrupted the state's monolithic development narrative by reframing resistance through Islamic theology. The study concludes that in post-authoritarian democracies, religious environmentalism offers a resilient form of counter-hegemony, providing a unique moral shelter for grassroots dissent where secular movements often falter.